Polymerization of meat and tempeh protein using transglutaminase and their potency as an antihipertency and antioxidant agent - Erwanto, Yuny (2010)
This research was done to explore meat and tempeh protein mixture as biopolymer materials and their potency as an antihipertency and antioxidant agent. Meat and tempeh protein contain many kinds of peptides which very useful for human health. Meat and fermented soybean protein can form crosslink bond using transglutaminase as a catalyst and will increase their ability as a food ingredients, antihypertency and antioxidant agent. Materials consisted of 5 groups of protein mixture between meat and tempeh (100 % meat : 0% tempeh, 95% meat : 5% tempeh, 90% meat : 10% tempeh, 85% meat : 15% tempeh and 80% meat : 20% tempeh, w/w) with 4 levels of transglutaminase enzyme concentrations (0.00; 0.02; 0.04 and 0.06%, w/w). Observed variables were protein polymerization, antihipertency and antioxidant activity. Biopolymer of meat-tempeh protein mixture was confirmed using electrophoresis method. Results showed meat-tempeh protein was able to form protein crosslinks using transglutaminase enzymes. Protein hydrolyzed of meat and tempeh mixture showed the ability to inhibit angiotensin converting enzyme, and both materials (meat and tempeh) had the potency as an antihipertency agent. The substitution of Meat protein with tempeh protein showed the increasing antioxidant activity with increasing tempeh addition level. In conclusion, tempeh contents protein and formed crosslinks bond with meat protein and the mixture protein was able to inhibit angiotensin converting enzyme and oxidations activity.